The influences of livestreaming on online purchase intention: examining platform characteristics and consumer psychology - Zhu, Peng (2023)
Purpose: Livestreaming, as a relatively new online marketing model, has generated numerous business opportunities for e-commerce and social commerce. The purpose of this paper is to investigate to what degree livestreaming content impacts online users' cognitive and emotional reactions and whether their cognitive and emotional responses affect their purchase intention. Design/methodology/approach: Through the lens of regulatory focus theory (RFT) and stimulus–organism–response (S–O–R) theory, the authors empirically examine the influencing mechanisms of livestreaming on online consumers' purchase intentions. Structural equation models are used to analyze the relationships in the proposed research model. Findings: The results of this study show that information-task fit positively affects consumers' perceived usefulness of livestreaming. Both visual effects and sociability positively affect consumers' perceived value and social presence. Furthermore, perceived usefulness and perceived joy positively affect consumers' purchase intentions in a livestreaming environment. This study’s results also demonstrate that the regulatory focus of consumers has a moderating effect on the influence of their perceived joy on shopping intentions. Originality/value: This study contributes to the relevant literature by simultaneously examining the role of e-commerce platform characteristics and online consumer psychology in influencing behavioral intention. With a better understanding of their role, platform operators and sellers can refine their livestreaming marketing tools and strategies. Highlighting the interplays among external stimuli, user reactions and user motivational styles, this study contributes to mobile e-commerce literature and the broader literature on digital marketing and human–computer interaction.